(3QSGdI aj CbhGd GdMceGA hGdTYQGA ef GdMces - (3LeGd GdOjf jGbhJ GdeSJYUej Hf YHO Gddg, GdOhej,J (B689 (3g` s ((3jGbhJ GdeSJYUei s)
(3ChdgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde(B:" (3eG GcJSH GMO CaVd ef Ybd jgOjg Edi gOi hjQOg Yf QOi(B" (3bjd dHgdhd(B: (3GJYO GdeLGfjf? abGd gPG jWhd hdcfi CYO GdYbdGA s
(3BNQgG (B:s
(3eHJhQ BNQ GdehLhO HgG HYO YHGQI(B((3bGd GHf YHGS (B: (3dh bfY GdfGS(B) (3HSWhQ (B: (3bGd MSGf Hf KGHJ s
(3hecJhH ai BNQ GdfSNI HGdaGQSjI Cf gPg GdQSGdI gi Chd eG cJHg jGbhJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs